Макроструктура англомовних фахових текстів сфери освіти - Закреницька, Л. (Філологічний дискурс, 2020)
У статті вивчаються засоби когезії англомовних фахових
текстів сфери освіти, визначаються характеристики
макроструктури фахового тексту за жанром. Виявлено граматичні,
лексичні, стилістичні та логічні засоби зв’язності фахових текстів,
визначено їх кількісні параметри та особливості використання з
огляду на тип тексту. The article studies the means of cohesion of English professional texts in the
field of education, it defines the characteristics of the macrostructure of the
professional text according to the genre. Grammar, vocabulary, stylistic and logical
cohesion of professional texts are identified, their quantitative parameters and usage
peculiarities are considered with regard to the type of text. Each kind of cohesion is
discussed in detail, its most dominant means are emphasized and exemplified by
examples from multi-genre professional texts.The results of the study are
systematized and presented in the table. The means of grammatical and lexical
cohesion have been found to prevail in the texts of scientific articles and textbooks of
various types, and lexical cohesion has been fixed as dominant in the texts of popular science magazines.